Development of an Edible Nanoparticle Coating to Limit the Effect of Moisture Loss on the Shelf Life of Beef - Gorokgaha Gedarawatte, Shamika Thushara (Curtin University, 2021)
The PhD investigated novel methods to extend the shelf-life of vacuum-packaged beef by reducing the moisture loss associated with purge and drip formation while maintaining eating quality. Using a combination of meat and material sciences, this study generated a comprehensive understanding of edible coatings’ interaction with the meat structure and developed a sustainable, ecofriendly packaging system.